Persepsi Kakitangan Sokongan Terhadap Penilaian Prestasi di Majlis Perbandaran Padawan, Kuching - Kueh, Kai Hua (Universiti Malaysia Sarawak, (UNIMAS), 1999)
The purpose of this study is to determine the perception of clerical and technical workers towards performance appraisal in Padawan Municipal Council. In this study, the difference in perception towards performance appraisal based on demographic characteristics was determined. Beside this, the study also focused on determining the relationship between perception and the factors that influenced workers' perception. These factors are trust and respect, common standard in performance appraisal for all workers, communication through dialogue, the importance of trained appraiser, the importance of follow-up, and the importance of continuous informal performance appraisal or verbal appraisal. Questionnaire is used collecting data from a sample of 73 respöndents. All respondents are in the clerical and technical categories or support groups. This study shows that there is no significant difference in the perception towards performance appraisal based on selected demographic characteristics. The finding indicates that 67.1 percent of workers have positive perception towards performance appraisal as practice in the council. Pearson Correlation's test shows that there is a significant relationship between performance appraisal and trust and respect, common standard in performance appraisal for all workers, communication through dialogue, the importance of trained appraiser, the important of follow-up, and the importance of continuous informal performance appraisal or verbal appraisal. This study indicates that all the six factors are crucial in the performance appraisal process. Thus, all these factors should be given consideration in implementing performance appraisal within the council. In conclusion, the finding of the study shows that many factors have to be considered in conducting performance appraisal. In this study, six major factors were found to have influenced the perception of workers towards performance appraisal. Thus, the management and the appraisers have to be more sensitive to these issues and try to understand how these factors work, so as to overcome and tackle the problems and challenges related to performance appraisal